KANDUNGAN LOGAM BERAT PADA AIR DAN TIRAM (Crassostrea cucullata Born) DI MUARA SUNGAI LOSKALA KOTA LHOKSEUMAWE PROVINSI ACEH - Irfan Emersida; Sukendi Sukendi; Bintal Amin (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
Analysis of heavy metals content Pb, Cu and Zn in sea water and Oyster (C.cucullata) in Loskala River Estuary has been conducted from July – August 2013.Samples of sea water andOyster (C. cucullata) were taken from five stations withthree replicates at each station. Heavy metals content analysis was carried out inthe KLH Pekanbaru Laboratory by using an Atomic AbsorptionSpectrophotometer Shimadzu AA-7000. The results showed that average haeavymetals content in sea waters were 0,077 μg/L (Pb), 0,045 μg/L (Cu) ), 0,125 μg/L(Zn) and in Oyster (C. cucullata) were 14,454 μg/g (Pb), 103,778 μg/g (Cu) ),111,611 μg/g (Zn) respectively. Simple linear regression analysis indicatespositive correlation between metals contentin sea water and in Oyster (C.cucullata) with Y =12,79+ 21,57X (r = 0,153) Pb ; Y = 8,384 + 2117X (r = 0,437)Cu and Y =93,76 +142,8X (r = 0,432) Zn.Keywords : Heavy Metal, Water, Oyster, Loskala River Estuary